Algoritma Naive Bayes untuk Memprediksi Waktu Pengerjaan Uji Kompetesi Keahlian (UKK) Siswa Sekolah Menengah Kejuruan - Mutaqin, Muhammad Zaenal; Mutoffar , Muhamad Malik (Program Studi Informatika Fakultas Ilmu Komputer Universitas Bhayangkara Jakarta Raya, 2023)
This research is motivated by the need for a method or method that helps teachers and schools to predict the speed of time for students UKK work so that schools are more effective in preparing students to face UKK with faster processing time where the current problem is that schools are still using manual prediction methods . The hypothesis of the researchers is that by implementing the Naïve Bayes algorithms to predict the length of time the UKK Student can work, it can produce more perfect predictions so that school management is more efficient in providing solutions for students who are predicted to work slowly on SMK Bhakti Persada Bekasi . UKK is the final assessment in order to determine the achievement of competencies for vocational students. The use of Data Mining with artificial classification and intelligence models that will predict the length of time spent on UKK in terms of student completion time quickly, normally or slowly. The Algorithm method used is Naïve Bayes with the prediction accuracy of 99.11%.